2004
DOI: 10.1038/ng1471
|View full text |Cite
|
Sign up to set email alerts
|

Rate of molecular evolution of the seminal protein gene SEMG2 correlates with levels of female promiscuity

Abstract: Postcopulatory sperm competition is a key aspect of sexual selection and is believed to drive the rapid evolution of both reproductive physiology and reproduction-related genes. It is well-established that mating behavior determines the intensity of sperm competition, with polyandry (i.e., female promiscuity) leading to fiercer sperm competition than monandry. Studies in mammals, particularly primates, showed that, owing to greater sperm competition, polyandrous taxa generally have physiological traits that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
252
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(269 citation statements)
references
References 25 publications
16
252
1
Order By: Relevance
“…Consistent with a hypothesis of sexual conflict (Stockley, 1997), recently mated females upregulate proteases thought to assist in plug degradation (Kelleher and Pennington, 2009;Dean et al, 2011), whereas male seminal fluid is enriched for protease inhibitors , although proteases and their inhibitors have additional roles in reproduction (Wolfner, 2002;Kawano et al, 2010). Also, plug-forming proteins, proteases and protease inhibitors all tend to evolve rapidly (Dorus et al, 2004;Clark and Swanson, 2005;Kelleher et al, 2007;Lawniczak and Begun, 2007;Ramm et al, 2008;Wong et al, 2008;Dean and Nachman, 2009;Dean et al, 2011) as predicted for genes involved in sexual conflict (Swanson and Vacquier, 2002;Clark et al, 2006). In primates, the evolutionary rate of a key copulatory plug gene, SEMG2, is positively correlated with the inferred intensity of sexual selection (Dorus et al, 2004;Ramm et al, 2009).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Consistent with a hypothesis of sexual conflict (Stockley, 1997), recently mated females upregulate proteases thought to assist in plug degradation (Kelleher and Pennington, 2009;Dean et al, 2011), whereas male seminal fluid is enriched for protease inhibitors , although proteases and their inhibitors have additional roles in reproduction (Wolfner, 2002;Kawano et al, 2010). Also, plug-forming proteins, proteases and protease inhibitors all tend to evolve rapidly (Dorus et al, 2004;Clark and Swanson, 2005;Kelleher et al, 2007;Lawniczak and Begun, 2007;Ramm et al, 2008;Wong et al, 2008;Dean and Nachman, 2009;Dean et al, 2011) as predicted for genes involved in sexual conflict (Swanson and Vacquier, 2002;Clark et al, 2006). In primates, the evolutionary rate of a key copulatory plug gene, SEMG2, is positively correlated with the inferred intensity of sexual selection (Dorus et al, 2004;Ramm et al, 2009).…”
Section: Introductionmentioning
confidence: 67%
“…Also, plug-forming proteins, proteases and protease inhibitors all tend to evolve rapidly (Dorus et al, 2004;Clark and Swanson, 2005;Kelleher et al, 2007;Lawniczak and Begun, 2007;Ramm et al, 2008;Wong et al, 2008;Dean and Nachman, 2009;Dean et al, 2011) as predicted for genes involved in sexual conflict (Swanson and Vacquier, 2002;Clark et al, 2006). In primates, the evolutionary rate of a key copulatory plug gene, SEMG2, is positively correlated with the inferred intensity of sexual selection (Dorus et al, 2004;Ramm et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…A number of seminal proteins in Drosophila, such as the accessory gland protein Acp26Aa, have been shown to exhibit rapid evolution and high ratios of non-synonymous to synonymous substitution, a hallmark of positive selection [10]. In mammals in general [11] and primates in particular [12], seminal proteins have been found to evolve rapidly and show evidence of positive selection related to sexual selection and sexual conflict. Sexual selection and sexual conflict are thus expected to act on the proteins that make up this locus of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, as major constituents of semen, the semenogelins are closely associated with reproduction, and a large proportion of our knowledge on these proteins consists of results and hypotheses related to fertility [16]. A correlation has been found between the degree of female promiscuity within a species and the evolution of the two genes encoding 3 semenogelins I and II, and thus it has been suggested that post-copulatory sperm competition drives the evolution of these genes [13,17,18]. In addition to having coagulum-forming functions and being susceptible to cleavage by kallikrein-like peptidases, the semenogelins are assumed to activate sperm hyaluronidase [19], affect sperm motility [20], possess antimicrobial activity [21], serve as substrates for transglutaminase [22], and have amyloid properties [23].…”
mentioning
confidence: 99%